Adapting the Academic Motivation Scale for Homeschool Students in Indonesia: A Study on Reliability, Validity, and Motivational Profiles - Susilo, Onggo; Chandra, Audrey Vivian; Rusijono, Rusijono; Mariono, Andi (LP. Ma'arif Janggan Magetan, 2024)
This study explores the adaptation of the Academic Motivation Scale (AMS) for Indonesian homeschool students using English as their second language. The primary objective was to assess the scale's reliability and validity in this unique educational context and to conduct a descriptive analysis of intrinsic, extrinsic, and amotivation scales. A sample of 26 students from Grades 7 to 11 participated, responding to an English-adapted AMS questionnaire. The findings revealed high internal consistency across all motivation scales, as indicated by Cronbach's alpha values (Intrinsic Motivation: 0.918, Extrinsic Motivation: 0.928, Amotivation: 0.868). Pearson correlation coefficients further supported the reliability of individual subscales. Descriptive analysis showed varying mean scores across different motivational dimensions. The study highlights the AMS's potential in diverse linguistic and educational settings, emphasizing the need for contextual adaptations. While the results affirm the scale's applicability in a homeschool environment, the study acknowledges limitations in sample size and suggests future research directions, including expanding the sample size and employing Confirmatory Factor Analysis for more comprehensive validation. This research contributes to the growing body of knowledge on academic motivation in alternative learning environments, particularly in the post-pandemic educational landscape.